(6 1/7)÷(1/7)-(4 3/5)×(15/23)+(1 1/8)÷(1/8)=
=(43/7)÷(1/7)-(23/5)×(15/23)+(9/8)÷(1/8)=
=(43/7)×(7/1)-(23/5)×(15/23)+(9/8)×(8/1)=
=(301/7)-(345/115)+(72/8)=
=43-3+9=49
По действиям:
(6 1/7)÷(1/7)=43/7÷1/7=43/7×7/1=301/7=43
(4 3/5)×(15/23)=23/5×15/23=345/115=3
(1 1/8)÷(1/8)=9/8÷1/8=9/8×8/1=72/8=9
43-3+9=49
(2u*2+3)*(3u-6)u*3
(4u+3)*(3u-6)u*3
(4u+3)*(3u-6)*3u
(12u²+9u) *(3u-6)
26u³-72u²+27u²-54u
36u³-45u²-54u
А) +16,192-11,817=+4,375
б) -16,192-11,817=-28,009
в) -16,192+11,817=-4,375
г)-25,48+64,201=+38,721
д)-25,48-64,201=-89,681
е)+25,48-64,201=-38,721
Корень из 45 примерно получится 6.7